(untitled) (Politeja, 2025)
PROVOCATION OR A LESSON IN TOLERANCE? THE GARDENER (2012) BY MOHSEN MAKHMALBAF AND ITS REPERCUSSIONS IN THE CONTEXT OF IRAN–ISRAEL RELATIONS The article explores the reasons for the split reception of The Gardener (2012), a documentary film directed by Mohsen Makhmalbaf. The film follows a filmmaker and his son as they travel to Israel to learn about the Baha’i Faith, a religion that originated in Iran but is banned there. It combines documentarystyle techniques with poetic visuals, reflecting on the role of religion in fostering peace or conflict. The film is notable to be made by an Iranian filmmaker in Israel, a bold move given the political tensions between the two countries. The Gardener gained worldwide attention and acclaim sparked backlash in the Islamic Republic of Iran and prompted a protest by pro Palestinian activists and intellectuals. The article aims to explain the reasons for these controversies in the context of Iranian-Israeli relations and to analyse the director’s message.